Providers’ Beliefs and Values: Understanding Their Approach to Gender-Affirming Care - Ahona Shirin; Maya Daniello; Laura Stamm (Journal of Primary Care & Community Health)
Objectives: This qualitative study explored the beliefs and values influencing healthcare providers’ delivery of gender-affirming care (GAC) to transgender and gender-diverse (TGD) youth amidst current social and political dynamics. Methods: The study PI conducted 43 semi-structured interviews with providers across states with varying GAC legislation. Responses from 41 providers were analyzed in this paper. A thematic approach to data analysis was employed using qualitative coding. Results: Key themes emerged: criteria for treatment, ethical and moral considerations, and professional and personal responsibility. Providers widely endorsed GAC as evidence-based and essential for alleviating distress and promoting autonomy. They emphasized the importance of respecting patients’ gender identities and viewing GAC as life-saving. Conclusion: Despite legislative challenges, the study highlights a strong consensus among providers on the medical necessity of GAC for TGD youth.